PERANCANGAN WEBSITE SEBAGAI MEDIA PROMOSI DAN INFORMASI PADA MADRASAH ALIYAH NEGERI PURWODADI - Muhamad Sodik; Sarwo Nugroho (STEKOM PRESS, 2016)
Madrasah Aliyah Negeri (MAN) Purwodadi is a formal educational institution located on Jl. P. Diponegoro No. 22, the direction of Jalan Purwodadi - Solo. MAN Purwodadi as one of the Secondary Education Institutions in Purwodadi has an important role in the future, in the context of increasing the intelligence of the nation while preparing students who are faithful and devoted and possessing Science and Technology which are characteristic of their Islam. Some agencies including educational institutions in an effort to improve the image both in terms of promotion and information now, have begun to use website media that can be quickly accessed widely so as to improve the quality of service to the community. MAN Purwodadi in the current promotion and information efforts still use the method of manually explaining which will certainly take time and effort and still use print media that has limited reach and requires more costs for each print each year. MAN Purwodadi until now does not have a new alternative media in the form of a website that follows the times that if not followed up will certainly be less competitive in terms of promotion and information. Therefore, it is necessary to have new alternative media that are effective and efficient and sustainable which in addition to increasing positive value for MAN Purwodadi, can also support and cover up the weaknesses of promotional media and information that has been used before. In this study data were collected through a questionnaire method of 30 respondents in potential students using a Likert scale to find out the responses of respondents to each variable. Then do the analysis of the data obtained in the form of quantitative analysis. From the analysis obtained product information level score of 390 or 32.5%; the effective level of the product is 222 or 18.5%; and the product efficiency level of 399 or 33.25%. From the existing score indicators, if added together the results will show the extent of the feasibility of the website as a promotional media and MAN Purwodadi information. From the results of this analysis it can be concluded that Website Design as a Media Promotion and Information on MAN Purwodadi is considered